TAVR Decreases Mortality When Compared with Surgery in High-Risk Patients - Cunningham, Muriel (MD Conference Express, 2014)
A large, prospective, randomized trial was conducted at 45 sites in the United States to compare the safety and efficacy of transcatheter aortic valve replacement (TAVR) with the CoreValve self-expanding prosthesis with surgical aortic-valve replacement (SAVR) in patients with severe aortic stenosis at high risk for cardiac surgery. This article presents the results from the patients in the high-risk cohort who were randomized to either CoreValve or surgery [Adams DH et al. N Engl J Med 2014].